Interactions among dietary fat, mineral status, and performance of endurance athletes: A case study - Lukaski, H. C.; Bolonchuk, W. W.; Klevay, L. M.; Milne, D. B.; Sandstead, H. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
We examined cyclists who consumed isoenergetic, isonitrogenous diets for 28-day periods in a randomized, crossover design in which dietary carbohydrate, polyunsaturated, or saturated fat contributed about 50% of daily energy intake. Peak aerobic capacity [62 ml/(kg á min)] was unaffected by diet. Endurance capacity at 70-75% peak aerobic capacity decreased with the polyunsaturated fat diet. Copper retention tended to be positive only with saturated fat. Less iron and zinc were retained (intake - losses), and fecal losses of these minerals increased with the polyunsaturated fat. Blood biochemical measures of trace element nutritional status were unaffected by diet, except serum ferritin, which tended to decrease during consumption of the polyunsaturated fat diet. These preliminary results suggest that diets high in polyunsaturated fat, particularly linoleic acid, impair absorption and utilization of iron and zinc, and possibly magnesium, and may reduce endurance performance.